(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2023)
The article explore the problems of ensuring the competitiveness of domestic enterprises. The purpose of the article is to develop recommendations for improving the quality of products as a basis for ensuring the competitiveness of domestic enterprises on the world market. Levels of competitiveness are given: product competitiveness, enterprise competitiveness, industry competitiveness, country competitiveness. The interdependence of different levels of competitiveness among themselves is substantiated. The competitiveness of the enterprise depends on the competitiveness of the products it manufactures. The competitiveness of the industry depends on the competitiveness of the enterprises operating in it. The competitiveness of the country depends on the competitiveness of the branches of its national economy. The low competitiveness of domestic enterprises provokes a low level of competitiveness of the national economy. In turn, the low competitiveness of domestic enterprises is caused by the low competitiveness of the products they manufacture, and the latter by their low quality. The low quality of products is caused by the moral and physical wear and tear of the fixed assets of domestic enterprises, the use of outdated technologies, the lack of sufficient financial resources, improper management of product quality, and the insufficient level of motivation of employees to produce high-quality products. It was concluded that updating the technical and technological base of domestic enterprises will contribute to the growth of quality and competitiveness of products. An important role in improving the quality and competitiveness of the products of domestic enterprises can be played by the introduction of the concept of general quality management, which is oriented towards the management of the enterprise, which involves not only the management of product quality, but also the quality of work in general with the active involvement of all personnel. At the core of the TQM concept is the development, maintenance and continuous improvement of quality to meet customer needs. This, in turn, will lead to an increase in the competitiveness of domestic enterprises and the efficiency of their functioning on the market.